179k views
5 votes
Help please!!!!!!!!!

Help please!!!!!!!!!-example-1

1 Answer

2 votes

Answer:


f\left(0\right)=\left(0\right)^2-4\left(0\right)=0-0=0


f\left(1\right)=\left(1\right)^2-4\left(1\right)=1-4=-3


f\left(2\right)=\left(2\right)^2-4\left(2\right)=4-8=-4


f\left(3\right)=\left(3\right)^2-4\left(3\right)=9-12=-3


f\left(4\right)=\left(4\right)^2-4\left(4\right)=16-16=0

Explanation:

Given the function


f\left(x\right)=x^2-4x

Putting x=0 in the equation to find f(0)


f\left(x\right)=x^2-4x


f\left(0\right)=\left(0\right)^2-4\left(0\right)=0-0=0

Putting x=1 in the equation to find f(1)


f\left(x\right)=x^2-4x


f\left(1\right)=\left(1\right)^2-4\left(1\right)=1-4=-3

Putting x=2 in the equation to find f(2)


f\left(x\right)=x^2-4x


f\left(2\right)=\left(2\right)^2-4\left(2\right)=4-8=-4

Putting x=3 in the equation to find f(3)


f\left(x\right)=x^2-4x


f\left(3\right)=\left(3\right)^2-4\left(3\right)=9-12=-3

Putting x=4 in the equation to find f(4)


f\left(x\right)=x^2-4x


f\left(4\right)=\left(4\right)^2-4\left(4\right)=16-16=0

User Stavros Angelis
by
5.6k points